Coronavirus in a patient with hepatitis C: case report - Lucas R. Mostardeiro; Ellen Cristine A. Antoniolli; Jady W. Xavier (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT In February 2020, the World Health Organization (WHO) named the infection with the new coronavirus, which appeared in December 2019 in China, as Covid-19, and defined it as a worldwide pandemic. There is not much evidence about the relationship between liver disease and Covid-19. Laboratory tests have played a fundamental role in confirming Covid-19, what is usually done by the polymerase chain reaction (PCR) sample. The present study reports the laboratory aspects of a patient with type C hepatitis diagnosed with Covid-19 with an unfavorable evolution, devoting special attention to laboratory tests that were almost normal.